Hyaluronic acid-functionalized zeolitic imidazolate framework-8 nanoparticles: A one-pot synthesis approach for breast cancer therapy - Gaayatri, Silvaraju; Nur Airin Syahira, Johari; Azren Aida, Asmawi; Rosniza, Razali; Fatmawati, Adam; Loo, Yan Shan; Nurul Akmarina, Mohd Abdul Kamal (Springer Nature, 2025)
Effective breast cancer chemotherapy is hindered by dose-limiting systemic toxicity and off-target effects of conventional chemotherapeutics. Here we report a one-pot, surfactant-free solvothermal synthesis of hyaluronic acid-functionalized Zeolitic Imidazolate Framework-8 nanoparticles (HA@nZIF-8). The physicochemical properties of both functionalized and non-functionalized nanoparticles were characterized using characterization techniques, including powder X-ray diffraction (PXRD), Fourier transform infrared (FTIR) spectroscopy, high-resolution transmission electron microscopy (HR-TEM), scanning electron microscopy (SEM), nitrogen adsorption–desorption isotherms, and thermogravimetric analysis (TGA). SEM measured well-dispersed nanoparticles (93.5 ± 14.4 nm), whereas HR-TEM gave an average size of 127.3 ± 18.9 nm. Brunauer–Emmett–Teller (BET) surface area was reduced by 30%, corresponding to a successful surface functionalization. The HA@nZIF-8 demonstrates inhibitory effects within human breast cancer cells, MCF-7 (IC50 = 21.5 ± 3.8 µg mL−1), and is selectively toxic towards cancer cells with a selectivity index (SI) of 3.8. This work indicates that surface functionalization of ZIF-8 using hyaluronic acid (HA) promotes promising in vitro cytotoxic effects with selective activity toward MCF-7 cells.